1992
DOI: 10.1002/ca.980050102
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial coverage of the coronary sinus and related veins

Abstract: The incidence and distribution of landmarks relating to the coronary sinus (c.s.) were evaluated in 240 human hearts. Special attention wasdirected to the myocardial coat of the c.s., the distribution and pattern of the cardiac veins, and their dimensions. In all specimens the myocardial coat of the C.S. also covered the adjacent 2 to 11 mm of the great cardiac vein. In 15% of cases this myocardial layer was thickened in a sphincter-like fashion, the edge of which was formed obliquely, in a crescent-like manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 12 publications
1
70
0
1
Order By: Relevance
“…A previous detailed anatomic study documented the presence of a myocardial cover of the coronary sinus in 240 human hearts. 16 In all specimens, the myocardial coat also covered the adjacent 2 to 11 mm of the great cardiac vein and was sometimes thickened in a sphincter-like fashion. The valve of Vieussens was found in 87% of cases, whereas the ostium of the oblique vein was a more constant marker for determining the beginning of the coronary sinus.…”
Section: Chauvin Connections Between Coronary Sinus and Left Atriummentioning
confidence: 87%
See 1 more Smart Citation
“…A previous detailed anatomic study documented the presence of a myocardial cover of the coronary sinus in 240 human hearts. 16 In all specimens, the myocardial coat also covered the adjacent 2 to 11 mm of the great cardiac vein and was sometimes thickened in a sphincter-like fashion. The valve of Vieussens was found in 87% of cases, whereas the ostium of the oblique vein was a more constant marker for determining the beginning of the coronary sinus.…”
Section: Chauvin Connections Between Coronary Sinus and Left Atriummentioning
confidence: 87%
“…12,13 In epicardial mapping studies, Boineau et al 14 confirmed such a breakthrough in the region of the coronary sinus. Scherlag et al 15 described a left atrial tract within the ligament of Marshall that originated from the coronary sinus ostium, and a study by Ludinghausen et al 16 reported the anatomic features of the myocardial cover of the coronary sinus. The precise features of this interatrial link through the coronary sinus have not been defined.…”
mentioning
confidence: 99%
“…In particular, connections between the muscular wall of the coronary sinus and the remnant of the vein of Marshall to the left atrium are common. 1,8,9 The Neighborhood Parts of the left atrial body, the entrances of the pulmonary veins, the atrial appendage, and the coronary sinus are in close vicinity to important structures that may be affected by interventional maneuvers that are carried out on and within the left atrium. The epicardial aspect of the left atrium, particularly in the region of the veno-atrial junctions, the interatrial groove, the roof, and the tract of the coronary sinus along the inferior wall, is covered by pads of fatty tissues.…”
Section: Interatrial Muscular Connectionsmentioning
confidence: 99%
“…The sleeve covers a length of 25-52 mm and increases in thickness toward the coronary sinus orifice. 8 Muscular continuity between venous walls and the posterior and inferior left atrial wall is common. 1,8,9 The free wall of the coronary sinus, however, is often thin and relatively unprotected.…”
mentioning
confidence: 99%
“…In one study of 143 patients, 62.9% presented the valve; in 73 patients the valve had a semilunar shape, in 10 cases a septal shape and in seven cases a shape like a crest [20]. In 39 procedures, there were difficulties SOUZA, FSO ET AL -Technical aspects of lead implantation for left ventricle pacing through the coronary sinus, using anatomic radiology and intracavitary electrography in the cardiac resynchronization therapy with the forward movement of the electrode through the coronary venous sinus, near to the junction of the great cardiac vein, a probable location of the Vissencius' valve as found in 87% of the studied cases by Lundinghausen et al [21], also demonstrating the importance of this valve in the implantation procedure of the coronary sinus electrode.…”
Section: Commentsmentioning
confidence: 99%